General Average and the York-Antwerp Rules: The historical quest for international conformity, the divisive effect of more recent amendments to the Rules and recommendations with regard to the way forward to regain more widespread acceptance of the Rules in today's global maritime industry - Ukattah, Chukwuechefu Okwudiri (Department of Commercial Law, 2021)
General average emerged as an independent mechanism in ancient times for the redistribution of losses incurred for the safety of the common maritime adventure from peril. Its robustness and efficiency as a risk and loss distribution device led to its recognition and incorporation in a plethora of medieval codes and the laws of many maritime states. As the concept evolved in different maritime states there emerged a divergence in the principles and practice of general average. The undesirability of a divergence in such a concept of international import led to the adoption of the York-Antwerp Rules by the maritime community as a tool for achieving uniformity. The York-Antwerp Rules have been amended periodically over the course of more than a century with the object of achieving greater uniformity in the law of general average and to keep abreast of developments in international trade and the maritime industry. The most recent revision of the York-Antwerp Rules adopted in 2004 (York-Antwerp Rules 2004), is the first revision adopted without a consensus amongst the majority of interested parties. Nine years after their adoption, the York-Antwerp Rules 2004 have failed to gain widespread acceptance and use in the maritime industry. An attempt by the Comité Maritime International to resolve the impasse on the use of the Rules at its 2012 Beijing Conference was unsuccessful and it was resolved instead to work towards the adoption of a new set of Rules at its next Conference in 2016. To ensure that the revision of the York-Antwerp Rules presented for acceptance at the 2016 Conference does not suffer the fate of the York-Antwerp Rules 2004 it is important that the mistakes made with regard to the York-Antwerp Rules 2004 are not repeated. Consequently, this thesis analyses the substantive revisions made in the York-Antwerp Rules 2004 to ascertain why other interested parties, particularly shipowning interests, are opposed to the York-Antwerp Rules 2004. This will assist in the recommendations to be made with regard to the substantive changes to the York-Antwerp Rules 2004 that could ensure the widespread acceptance of the Rules to be adopted in 2016. Furthermore, the factors that led to the periodic revision of the Rules are examined and the ingredients of the previous successful revision processes are identified as a comparative base to ascertain the flaws, if any, in the process that led to the adoption of the York-Antwerp Rules 2004; which culminated in the lack of widespread acceptance of the Rules in the maritime industry. This thesis contends, among other things, that the York-Antwerp Rules 2004 failed to gain widespread acceptance in the maritime industry because the substantive changes introduced by the Rules did not ensure a measure of equitable balance of the interests of all interested parties. Furthermore, the ingredients of the previous successful revision processes were disregarded in the process of adopting the 2004 Rules. This thesis makes recommendations on the content of the York-Antwerp Rules to be adopted in 2016 and the process of adopting the new Rules in an attempt to enhance their widespread acceptance and use in the maritime industry.